2012
DOI: 10.1021/jf301457k
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Equivalence of Barleys Differing Only in Low- and Normal-Phytate Levels

Abstract: Recent breeding advances have led to the development of several barley lines and cultivars with significant reductions (50% or greater) in phytate levels. Low-phytate (LP) grain is distinguished by containing not only a reduced level of phytate P but also an increased level of inorganic P, resulting in greater bioavailability of P and mineral cations in animal diets. It is important to determine whether other nutritional characteristics are altered by breeding for the low-phytate trait. This study was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The variety HB340 (CDC Alamo), CDC Candle, and HB 335 (CDC McGwire) had the highest lipid contents in the whole grain whereas HB340 (CDC Alamo) was the highest in the 35% pearling flour. This finding is in agreement with the results of Moreau and others () who also found the lipid content of CDC Alamo to be higher than that of the other varieties they studied. The lipid content of the 35% pearling flour was substantially lower than that observed in a separate study conducted in our lab focusing on different levels of pearling (unpublished data), where a lipid content of 11.7% was obtained for 15% pearling flour of a different hulless double waxy barley variety (SB94794).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The variety HB340 (CDC Alamo), CDC Candle, and HB 335 (CDC McGwire) had the highest lipid contents in the whole grain whereas HB340 (CDC Alamo) was the highest in the 35% pearling flour. This finding is in agreement with the results of Moreau and others () who also found the lipid content of CDC Alamo to be higher than that of the other varieties they studied. The lipid content of the 35% pearling flour was substantially lower than that observed in a separate study conducted in our lab focusing on different levels of pearling (unpublished data), where a lipid content of 11.7% was obtained for 15% pearling flour of a different hulless double waxy barley variety (SB94794).…”
Section: Resultssupporting
confidence: 93%
“…Moreau and others (, ) investigated the tocol composition of barley grains and fractions obtained by scarifying. More recently, Moreau and others () showed that there were no significant differences in the levels of various components, including tocols, except for phytate for the 5 low‐ and 5 normal‐phytate barley cultivars grown in 3 Idaho locations. In the current study, the tocol contents and tocol compositions of 20 different varieties grown in Alberta were investigated.…”
Section: Introductionmentioning
confidence: 98%
“…To identify the biosynthetic pathway of PA and reduce the PA content in the grain, low phytic acid (lpa) mutants of wheat [10], maize [11][12][13], soybean [14,15], barley [16][17][18], and rice [19] have been used. These mutants have disrupted PA biosynthesis genes and exhibit low PA accumulation in the grains; however, in most cases, these mutants showed a significant reduction in germination and yield [20].…”
Section: Introductionmentioning
confidence: 99%
“…Barley is one of the earliest cultivated cereal grains in the World, which is attracting renewed interest for its use in food and as a bioethanol feedstock [1]. It is a preferred grain for cultivation in many areas in the World due to its resistance to drought and ability to mature in climates with a short growing season [2].…”
Section: Introductionmentioning
confidence: 99%